2000
DOI: 10.1007/s001220050038
|View full text |Cite
|
Sign up to set email alerts
|

Determining environmental covariates which explain genotype environment interaction in winter wheat through probe genotypes and biadditive factorial regression

Abstract: sured environmental variates (van Eeuwijk, 1995). Just as with AMMI, BIAREG provides axes or synthetic Genotype ϫ environment interaction is a commonly observed pheenvironmental variates to which genotypes differ maxinomenon in experiments in plant breeding and genetics. This interaction can be modeled by different statistical models which can include mally in sensitivity, but under the restriction of being covariates, such as in biadditive factorial regression, or in other ways, linear combinations of the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…Higher percentages were found for potato, soybean [Glycine max (L.) Merr. ], pea, wheat, maize and sorghum (Baril et al, 1995;Sneller et al, 1997;Brancourt-Hulmel et al, 2000;Abush, 2001;Alberts, 2004;Das et al, 2012), while similar percentages were reported for maize (Ajibade et al, 2003) and winter/spring wheat (Voltas et al, 2005).…”
Section: Tablesupporting
confidence: 72%
See 1 more Smart Citation
“…Higher percentages were found for potato, soybean [Glycine max (L.) Merr. ], pea, wheat, maize and sorghum (Baril et al, 1995;Sneller et al, 1997;Brancourt-Hulmel et al, 2000;Abush, 2001;Alberts, 2004;Das et al, 2012), while similar percentages were reported for maize (Ajibade et al, 2003) and winter/spring wheat (Voltas et al, 2005).…”
Section: Tablesupporting
confidence: 72%
“…Indeed, the observed percentage was higher than that found in other crops, such as potato, winter wheat, pea (Pisum sativum L.), maize and sugarcane (Baril et al, 1995;Brancourt-Hulmel et al, 2000;Taye et al, 2000;Admassu et al, 2008;Ramburan et al, 2011). Similar percentages were otherwise reported for maize [Zea mays L.], sorghum [Sorghum bicolor L. Moench] and winter/spring wheat (Ajibade et al, 2003;Alberts, 2004;Voltas et al, 2005;Das et al, 2012).…”
Section: Tablementioning
confidence: 51%
“…It has been proposed that the AMMI model and biplot were useful methods for the analysis of GE interactions (Ebdon andGauch 2002, Brancourt-Hulmel andLecomte 2003). The AMMI model had been exploited in the variety evaluation of soya bean (Zobel et al 1988), barley (van Oosterom et al 1993, wheat (Vargas et al 1999), rice and pigeonpea (Wamatu and Thomas 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to address this defi ciency, Yan and Tinker (2005) recently suggested a covariate-eff ect biplot which is generated from the fi rst two PCs of SVD of correlations of target trait (say yield) with every other trait in each of the test environments. To examine eff ects of both genetic and environmental covariables and to develop functional relationships and predictability with explanatory covariables, factorial regression or partial least squares analysis (e.g., Vargas et al, 1999;Brancourt-Hulmel and Lecomte, 2003;van Eeuwijk et al, 2005) may be more useful. These other explanatory traits may be replaced or augmented by other genetic covariables, such as quantifi cations of pedigree information, presence/absence of QTLs, or gene expression profi les in a microarray.…”
Section: Issue 5: How Relevant Is the Biplot Analysis To Understandinmentioning
confidence: 99%